Analisis Faktor-Faktor Psikologis Penyebab Kriminalitas Universitas Bhayangkara Jakarta Raya - Anggara, Irfan Zhikri; Zahira, Zalfa Hulwah; Martono, Sigit; Aprilia, Jihan; Supriyadi, Tugimin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Crime is an activity that violates norms and laws and harms other people, such as abuse, drug abuse, theft and immoral acts. This criminal activity is influenced by various factors, both internal and external. Internal factors include psychological factors that an individual has and external factors include the individual's economic and social environment. This research uses a literature review method by collecting, analyzing, evaluating and combining information from related scientific literature. The conclusion of this research is that there are various psychological factors that cause criminal behavior such as instinct (id), emotion, environment, trauma.